In silico study of amyloid β-protein folding and oligomerization - Urbanc, B. (National Academy of Sciences, 2004)
Experimental findings suggest that oligomeric forms of the amyloid β protein (Aβ) play a critical role in Alzheimer's disease. Thus, elucidating their structure and the mechanisms of their formation is critical for developing therapeutic agents. We use discrete molecular dynamics simulations and a four-bead protein model to study oligomerization of two predominant alloforms, Aβ40 and Aβ42, at the atomic level. The four-bead model incorporates backbone hydrogen-bond interactions and amino acid-specific interactions mediated through hydrophobic and hydrophilic elements of the side chains. During the simulations we observe monomer folding and aggregation of monomers into oligomers of variable sizes. Aβ40 forms significantly more dimers than Aβ42, whereas pentamers are significantly more abundant in Aβ42 relative to Aβ40. Structure analysis reveals a turn centered at Gly-37–Gly-38 that is present in a folded Aβ42 monomer but not in a folded Aβ40 monomer and is associated with the first contacts that form during monomer folding. Our results suggest that this turn plays an important role in Aβ42 pentamer formation. Aβ pentamers have a globular structure comprising hydrophobic residues within the pentamer's core and hydrophilic N-terminal residues at the surface of the pentamer. The N termini of Aβ40 pentamers are more spatially restricted than Aβ42 pentamers. Aβ40 pentamers form a β-strand structure involving Ala-2–Phe-4, which is absent in Aβ42 pentamers. These structural differences imply a different degree of hydrophobic core exposure between pentamers of the two alloforms, with the hydrophobic core of the Aβ42 pentamer being more exposed and thus more prone to form larger oligomers.